2012
DOI: 10.1371/journal.pone.0035533
|View full text |Cite
|
Sign up to set email alerts
|

Homeodomain-Interacting Protein Kinase (HIPK)-1 Is Required for Splenic B Cell Homeostasis and Optimal T-Independent Type 2 Humoral Response

Abstract: The homeodomain-interacting protein kinase (HIPK) family is comprised of four highly related serine/threonine kinases originally identified as co-repressors for various homeodomain-containing transcription factors. The HIPKs have been shown to be involved in growth regulation and apoptosis, with numerous studies highlighting HIPK regulation of the tumor suppressor p53. In this study, we have discovered a B cell homeostatic defect in HIPK1-deficient (HIPK1−/−) mice. Lymphopoietic populations within the thymus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Using this 3D chromatin-promoter interaction landscape, we were able to connect the promoters of 18,669 genes (associated with 79,330 transcripts) to their potential regulatory elements, representing 145,568 distinct gene-OCR interactions. Roughly half (47%, 68,229) of these occur in both cell types, while 24% (34,928) occur uniquely in naive cells, and 29% (42,411) are only found in TFH (Fig. 5a).…”
Section: Resultsmentioning
confidence: 99%
“…Using this 3D chromatin-promoter interaction landscape, we were able to connect the promoters of 18,669 genes (associated with 79,330 transcripts) to their potential regulatory elements, representing 145,568 distinct gene-OCR interactions. Roughly half (47%, 68,229) of these occur in both cell types, while 24% (34,928) occur uniquely in naive cells, and 29% (42,411) are only found in TFH (Fig. 5a).…”
Section: Resultsmentioning
confidence: 99%
“…Among these are HIPK1 , a nuclear homeobox-interacting protein kinase that cooperates with homeobox, p53, and TGFB/Wnt pathway transcription factors to regulate gene transcription 30, 3739 . A role for HIPK1 in T-independent B cell responses has be identified in the mouse 40 , but no role for this kinase has been previously established in TFH or SLE. Another gene implicated in our study is MINK1 , which encodes the misshapen-like kinase MAP4K6.…”
Section: Discussionmentioning
confidence: 99%
“…Erythroid cells that lack KLF3 or have reduced HIPK2 both fail to mature correctly, and it has been shown that KLF3-and HIPK1-deficient mice each have enlarged spleens, most likely as a consequence of compensatory stress erythropoiesis (9,54).…”
Section: Figure 12 Hipk2 Potentiates Klf3 Mediated Gene Repression Imentioning
confidence: 99%
“…There is also evidence that KLF3 and HIPK are components of the signaling pathways lying downstream of the B cell receptor that influence B cell development and activity (12,13,54).…”
Section: Figure 12 Hipk2 Potentiates Klf3 Mediated Gene Repression Imentioning
confidence: 99%